“Bida ba ang Saya sa Makabagong Teknolohiya?: An Assessment of Technological Advancements Implementation in Filipino Food Industry” - Samaniego, Merie Blaize A. (Animo Repository, 2023)
The study conducted by American Dining Creations (n.d.) sheds light on the increasing demand for food brought about by the global population surge, it reveals that people are not only interested in food but also in food services that are safer, faster, and convenient. The main objectives of this study are to identify the different technological advancements present in the food industry in Bacoor and to recognize its work performance. This study also aims to determine its impacts on customers’ level of satisfaction. A descriptive quantitative research design was employed to gather data to determine the perceptions and impacts of implementing robotic technologies on fast food chains. To obtain the required data, survey questionnaires were distributed to 147 customers presently dining in a fast-food restaurant in Bacoor, Cavite, Philippines. The study found that ordering kiosks were the most widely used technology, while robot servers were not yet available in the studied food outlets. Since these technologies offer accessibility, convenience, attractiveness, and innovativeness, the study concludes that its weaknesses do not outweigh its benefits in terms of work performance. While most respondents enjoy the benefits of these technologies, some did not strongly agree with them.